Tailoring natural-based oleogels combining ethylcellulose and virgin coconut oil - Silva, Simone S. (2022)
Oleogels are becoming an attractive research field, since they have recently been shown to be feasible for the food and pharmaceutical sectors and provided some insights into the biomedical area. In this work, edible oleogels were tailored through the combination of ethylcellulose (EC), a gelling agent, with virgin coconut oil (VCO), vegetable oil derived from coconut. The influence of the different EC and VCO ratios on the structural, physical, and thermal properties of the oleogels was studied. All EC/VCO-based oleogels presented a stable network with a viscoelastic nature, adequate structural stability, modulable stiffness, high oil-binding capability, antioxidant activity, and good thermal stability, evidencing the EC and VCOâ s good compatibility.